Optimasi Data Tembakau: Inovasi Berkelanjutan untuk Pengembangan Bisnis Tembakau Lombok Timur - Baiq Sari; Nurhami Ninda; Nurul Sakbaini; Karina Utami; Herie Saksono (ALETHEIA: Jurnal Sosial & Humaniora, Inovasi, Ekonomi, dan Edukasi, 2024)
This study discusses the development of tobacco commodity-based businesses originating from East Lombok Regency. The method is to optimize tobacco farming data (people/Rajang and Virginia). This research is based on the need for a balance between economic growth, environmental sustainability, and social welfare in the development of the tobacco sector. The main problems identified are fluctuations in tobacco harvest area, production dynamics, productivity gaps, and optimization of the added value of tobacco which are expected to have an impact on community welfare. Therefore, the question asked is how to optimize the use of data on tobacco harvest area, production, and productivity in East Lombok Regency which is suitable for business development. The method used is a quantitative approach with time-series data from 2014-2022. Data was obtained from the West Nusa Tenggara Province Central Statistics Agency and the NTB One Data Portal. Data analysis was carried out using descriptive statistical techniques and CAGR to measure the annual growth rate. The results of the research show that the production and harvest area of ​​smallholder and Virginia tobacco in East Lombok experienced significant growth, although there were fluctuations in certain years. Tobacco productivity also shows an increase, but it is not consistent. These results indicate that there is great potential in developing a more optimal tobacco business through the application of precision agricultural technology and product innovation. In conclusion, optimizing the use of agricultural data can support increasing production and welfare of tobacco farmers. The recommendations provided include synergy between the (Central) Government and the Regional Government of NTB Province as well as Regency/City Governments in the NTB Province region, increasing farmer capacity, forming farmer corporations, partnerships with investors, and implementing precision agricultural technology to ensure sustainability and efficiency in tobacco production.